EDUCATION ON THE PREVENTION OF HYPERTENSIONTO AVOID COMPLICATIONS IN THE CLINIC ROOM OF THE ACEH BESAR HOSPITAL - Edy Cahyady; Rizkidawati Rizkidawati; Nanda Desreza (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
Hypertension is currently known as the ‘silent killer’ because it is not often found with obvious signs and symptoms. Risk factors for hypertension include family genetic history, overweight or obesity, lack of physical activity, unhealthy lifestyle, alcohol consumption, and stress. The purpose of the activity is to increase public understanding in the prevention of hypertension in order to avoid its complications. This activity was held in the polyclinic room of the Aceh Besar Hospital. Participants who attended directly were patients who visited the hospital for re-control and treatment with a total of 17 patients. This community service method was carried out in the form of counselling and discussion. This activity was carried out on 25 April 2024 in the hospital poly room at 09.30 WIB until completion. The activity began with recording the participants and continued with the presentation of the objectives of the activity and material related to hypertension and its complications. From the activity it was found that the patient's level of understanding of poor diet was low in fibre, low physical activity, the use of excess salt content in cooking. It is recommended that people with hypertension can improve their lifestyle, diet, rest patterns that are not appropriate, and for families to continue to provide strong motivation to sufferers.